SCREENING OF NINE HERBAL PLANTS FOR ALPHA-AMYLASE INHIBITION - CHAKRABARTI, RITUPARNA; SINGH, BHAVTARAN; VN, PRAKRITH; VANCHHAWNG, LALTHANZAMA; THIRUMURUGAN, KAVITHA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the Î±-amylase inhibitory potential of nine herbal plants in regulating postprandial hyperglycemia. Materials and Methods: In vitro Î±-amylase inhibition assay using starch-iodine was performed. Î±-amylase inhibition delays breakdown of starch and prevents glucose release to reduce postprandial hyperglycemia. Results: The plants screened were Artocarpus altilis, Aconitum heterophyllum, Acorus calamus, Berberis aristata, Cassia auriculata, Cyprus rotundus, Mesua ferrea, Plumbago zeylanicum and Terminalia arjuna. Positive control Acarbose showed IC50 at 14.24 Î¼g/ml. Methanolic extract of C. auriculata (flower), T. arjuna (bark) and P. zeylanicum (rhizome) exhibited the best inhibitory activity with IC50 value of 37.28 Î¼g/ml, 48.75 Î¼g/ml and 68.66 Î¼g/ml, respectively. Conclusion: From the present study, we conclude that C. auriculata flower had displayed maximum inhibition against Î±-amylase. Keywords: Herbal plants, Hyperglycemia, Î±-amylase inhibition.